SEISMIC VULNERABILITY ASSESSMENT OF REINFORCED CONCRETE STRUCTURES IN KURDISTAN REGION-IRAQ - ASKAR, MAND; ABDUKA, KAMIRAN; ASKAR, LAWEND (Journal of Duhok University, 2020)
Earthquakes are one of the most destructive natural disasters that cause losses of life, damage to infrastructure and economic issues. Therefore, seismic risk assessment is essential for disaster mitigation, disaster management, and emergency preparedness. Seismic vulnerability is one of the major factors for evaluating the risk of earthquakes on reinforced concrete (RC) buildings. Seismic vulnerable RC buildings are buildings located in a seismic region and either designed with an outdated design code or designed without consideration for seismic activity. In the Kurdistan region of Iraq, most of the existing RC buildings do not meet the typical current seismic standard requirements as the region was expected as non-seismic region and followed the Iraqi seismic zone which considered as a low seismic region, therefore these type of buildings is expected to suffer extensive damage during strong earthquakes. Vulnerable RC buildings should be assessed in order to prevent future damage and new designed buildings need to meet such codes. Previous studies, conducted assessment of four to six stories structures in order to evaluate seismicity and to increase ductility of the evaluated structures based on member size. In this research, an existing 8-storey RC building, located in Duhok governorate- Kurdistan region of Iraq, is redesigned and evaluated. SeismoStruct V6.5 software was utilized for the purpose of simulating ductility and detailing for the existing structure using pushover analysis. The ductility of the existing and the proposed redesigned buildings then evaluated by obtaining inter-story drift and displacement based on capacity curve. The original design is further evaluated in terms of reinforcement ratio and detailing by redesigning the existing building in accordance with the ACI code 318, 2014 and using ETABS software version 9.7 for analysing. Nonlinear static pushover analysis is used for seismic performance evaluation. Inelastic static analysis procedures include capacity spectrum method and displacement coefficient method. The structure is then analyzed to observe the yielding of the members and the adequacy of the structural strength. The extent of damage experienced by the structure at the target displacement represents the damage that would be experienced by the building when it is subjected to an earthquake. As a conclusion, the redesigned structure showed 30% increasing in displacement when loaded in x- direction based on both ultimate and calculated base shear while the increase in displacement was around 10% when loaded in the y-direction. This displacement increase led into improving the ductility in the redesigned structure.